Is European monetary policy appropriate for the EMU member countries?: a counterfactual analysis - Bernd Hayo (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2006)
This paper analyses whether interest rate paths in the EMU member countries would have been different if the previous national central banks had not handed over monetary policy to the ECB. Using estimates of monetary policy reaction functions over the last 20 years before the formation of EMU, we derive long-run rules the relate interest rate setting to the expected one-year ahead inflation rate and the current output gap. These Taylor rules allow to derive long-run target rates which are employed in the simulation of counterfactual interest rate paths over the time period January 1999 to December 2004 and then compared to actual short-term interest rates in the euro area. It is found that for almost all EMU member countries euro area interest rates tend to be below the national target interest rates, even after explicitly accounting for a lower real interest rate in the EMU period, with Germany being the only exception.
Keywords: E5; 330; Taylor rule; monetary policy; ECB; European Monetary Union; Europäische Integration; Europäische Wirtschafts- und Währungsunion; Zentralbank; Geldpolitik; EU-Staaten